2020
DOI: 10.1002/jmv.26332
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 diagnostics in the virology laboratory of a University Hospital in Rome during the lockdown period

Abstract: Italy was one of the most affected nations by coronavirus disease 2019 outside China. The infections, initially limited to Northern Italy, spread to all other Italian regions. This study aims to provide a snapshot of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) epidemiology based on a single‐center laboratory experience in Rome. The study retrospectively included 6565 subjects tested for SARS‐CoV‐2 at the Laboratory of Virology of Sapienza University Hospital in Rome from 6 March to 4 May. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Italy has experienced one of the harshest and earliest COVID-19 (coronavirus disease 2019) epidemics, with the number of patients infected following, from the end of February up to the end of March 2020, an exponential trend [1] . Between the 6 March 2020 and 2 May 2020, a total of 394 patients were confirmed positive for SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) at the University Hospital of Rome Policlinico Umberto I (PUI) (Rome, Italy) [2] . At the PUI, 5 COVID-19-devoted wards were organised, including two brand-new intensive care units (ICUs), counting 32 dedicated to COVID-19 patients: the first was the old general ICU converted into a dedicated COVID-19 ICU, while the second was created in the spaces of four operating rooms (new ICU).…”
Section: Klebsiella Pneumoniae Infections In Covid-19 Patients: a 2-month Retrospective Analysis In An Italian Hospitalmentioning
confidence: 99%
“…Italy has experienced one of the harshest and earliest COVID-19 (coronavirus disease 2019) epidemics, with the number of patients infected following, from the end of February up to the end of March 2020, an exponential trend [1] . Between the 6 March 2020 and 2 May 2020, a total of 394 patients were confirmed positive for SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) at the University Hospital of Rome Policlinico Umberto I (PUI) (Rome, Italy) [2] . At the PUI, 5 COVID-19-devoted wards were organised, including two brand-new intensive care units (ICUs), counting 32 dedicated to COVID-19 patients: the first was the old general ICU converted into a dedicated COVID-19 ICU, while the second was created in the spaces of four operating rooms (new ICU).…”
Section: Klebsiella Pneumoniae Infections In Covid-19 Patients: a 2-month Retrospective Analysis In An Italian Hospitalmentioning
confidence: 99%
“…None of the patient had shown any neurological symptoms before death in our study. SARS-CoV-2 wasn't found in study of Turriziani O et al [24] (5 cases) and Neumann B et al [25] (30 cases). Destras G et al [26] tested 578 CSF samples of 555 patients received at Lyon university hospital during covid-19 epidemic.…”
Section: Resultsmentioning
confidence: 92%
“…Bennet D et al [20] described case report of 61 year old renal transplant patient, who had shown presence of SARS-CoV-2 in plural uid by RT-PCR. SARS-CoV-2 was also detected from pleural uid in study done by Malik MI et al [21] (1 case), Mei F et al [22] (1 case), Baek MS et al [23] (1 case) and Turriziani O et al [24] (3 out of 8 cases). As pleural mesothelial cell expresses DPP4 (CD26) receptor, which plays a role for entry of a virus inside the cell, pleura is target for SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Oropharyngeal swabs collected from 150 individuals, 112 symptomatic COVID-19 patients and 38 healthcare workers not infected by SARS-CoV-2, were tested for KIPyV and WUPyV DNA presence. Diagnosis of SARS-CoV-2 was previously performed by real-time RT-PCR assay (RealStar SARS-CoV2 RT-PCR, Altona Diagnostics) [15] from March 2020 to May 2020 at Policlinico Umberto I Hospital, Rome, Italy. Viruses identified in each specimen were documented and summarized as co-infection, single infection or negatives.…”
Section: Study Population and Sample Collectionmentioning
confidence: 99%